Impact of characteristics of the urban homes on greenhouse gas emissions in Ibagué, Colombia (2022)
The impact of some sociodemographic and socioeconomic characteristics of urban households in the city of Ibagué on greenhouse gas (GHG) emissions from electricity consumption and use of fossil fuels for transportation and food preparation was examined. A semi-structured survey was conducted in 1,816 households in the city of 170,170. GHG emissions in households in Ibagué are significantly related to socioeconomic status, household size, and household composition (p<0.01). The emissions per household in socioeconomic stratum 2 are the lowest, however for the year 2018 they contributed 41% of the emissions. Cities require behavior-based mitigation strategies and nature-based solutions to reduce CO2 emissions from electricity consumption and the use of fossil fuels.